2023
DOI: 10.1002/mc.23538
|View full text |Cite
|
Sign up to set email alerts
|

LATS‐regulated nuclear‐cytoplasmic translocation of SREBP2 inhibits hepatocellular carcinoma cell migration and invasion via epithelial–mesenchymal transition

Abstract: Abnormal cholesterol synthesis plays a crucial role in the development of hepatocellular carcinoma (HCC). Sterol regulatory element-binding protein 2 (SREBP2) is involved in cholesterol synthesis by translocating to the nucleus where it stimulates the transcription of genes encoding enzymes involved in the cholesterol synthesis pathway. However, the function and regulatory mechanism of SREBP2 in HCC remain unclear. In this study, we aimed to gain a better understanding of the effects of SREBP2 and its function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Epithelial–mesenchymal transition (EMT) plays an important role in the heterogeneity and tumor metastasis. SREBP2 promoted HCC cells invasion and metastases by inducing EMT [ 26 ]. Moreover, recent studies have shown that XBP1-u promoted tumorigenesis.…”
Section: Gene Involved In Cholesterol Metabolism In Hepatocellular Ca...mentioning
confidence: 99%
“…Epithelial–mesenchymal transition (EMT) plays an important role in the heterogeneity and tumor metastasis. SREBP2 promoted HCC cells invasion and metastases by inducing EMT [ 26 ]. Moreover, recent studies have shown that XBP1-u promoted tumorigenesis.…”
Section: Gene Involved In Cholesterol Metabolism In Hepatocellular Ca...mentioning
confidence: 99%